2011
DOI: 10.1007/978-3-642-23333-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Measure to Improve: A Study of eParticipation in Frontrunner Dutch Municipalities

Abstract: Abstract. eParticipation is still in its early phases of development, in which government organizations undertake many experiments. There is no systematic overview of these experiments, which inhibits learning from each other. Measuring and benchmarking eParticipation provide the opportunity to inspire new developments by sharing best practices. This paper presents the development of a measurement instrument that is subsequently used to investigate eParticipation in frontrunner Dutch municipalities. This instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To overcome the first of the mentioned limitations, both specialized models (e.g. Concha et al , 2012; Veljković et al , 2014; Veenstra et al , 2011) and multidimensional models (e.g. Dias, 2011; Dias and Costa, 2013) have been developed.…”
Section: Theoretical Referencesmentioning
confidence: 99%
“…To overcome the first of the mentioned limitations, both specialized models (e.g. Concha et al , 2012; Veljković et al , 2014; Veenstra et al , 2011) and multidimensional models (e.g. Dias, 2011; Dias and Costa, 2013) have been developed.…”
Section: Theoretical Referencesmentioning
confidence: 99%
“…investigating 15 large European cities found that local governments are not utilizing to a great extent social media platforms. Low to moderate usage of social media platforms by local governments were also found in countries like Germany Van Veenstra et al 2011 ), Sweden (Larsson 2013 ), Finland (Christensen 2013 ), and Italy . In a similar vein, municipalities in Egypt have been exploiting social media in their web pages quite slowly ) while poor levels of interactive communication were also found in the websites of several Mexican local government authorities .…”
Section: Introductionmentioning
confidence: 99%
“…Twitter), video platforms (e.g. YouTube), discussion forums, blogs and chats (Gibson & Ward, 2000;Macintosh, 2008;Schweitzer, 2005Schweitzer, , 2010Tambouris et al, 2007;van Veenstra et al, 2011): Because 46 percent of Swiss internet users access online communication from mobile tools (Latzer et al, 2013), we also coded mobile apps offered by the cities. We also included online-surveys because they are intended to generate popular feedback; newsletters and RSS feeds, because they require subscription, and blogs or wikis, because they may be primarily content sharing sites (Go & You, 2016), but invite user feedback nevertheless.…”
Section: Table 1: About Herementioning
confidence: 99%
“…Thus, interactive communication implies that two-way communication actually takes place, while interactive media only provide the necessary means for two-way communication. For this study we rely on previous research that have defined and differentiated types of interactive online media (Gibson & Ward, 2000;Macintosh, 2008;Schweitzer, 2005Schweitzer, , 2010Tambouris, Liotas, & Tarabanis, 2007;van Veenstra, Janssen, & Boon, 2011). Previous studies have also underlined the potential inherent in digital media to change (even augment) the relationship between governments, organizations and the public at large, providing new and more opportunities for connecting and dialoguing (e.g.…”
Section: Introductionmentioning
confidence: 99%